Dispersi Kompensasi Kinerja Tinggi dengan Apodization Chirped Fiber Bragg Grating untuk Sistem Komunikasi Fiber - Dedi Irawan; Azhar Azhar; Khaikal Ramadhan (Postgraduate, University of Mataram, 2022)
The effect of dispersion will interfere with the signal transmission. Several ways can be done in compensating the dispersion such as by utilizing dispersion compensator fiber (DCF) or chirp fiber Bragg grating (CFBG). The dispersion compensation schemes with DCF are expensive and it also causes nonlinear optical effects, meanwhile, the CFBG can reduce costs and promise better results. In this study, an Apodization Chirped Fiber Bragg Grating (ACFBG) has been developed as a dispersion compensator with Optisystem with non-return to zero (NRZ) 20 Gbps. It is found that the Gaussian Cubic-CFBG apodization with a size of 90 mm had the highest Q-factor evaluation ofÂ 20,776 dB for a 250 km dispersion compensation scheme. this result is much larger than the previous CFBG dispersion compensation scheme. This study also confirmed that the Gaussian Apodization was the best profile compared to Tanh Apodization, from the evaluation of the Q-factor, Tanh cubic-CFBG only obtained a Q-factor of 9.6 dB. Certainly, the high performance of ACFBG as a dispersion compensator is very useful to support optical communication systems